Analysis of the Challenges and Opportunities of the Merdeka Curriculum at MI Arrahman School Palembang - Nurjanah, Diana; Lutfiah Harnum Azzahra; Vivin Stelora; Abdurrahamansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Merdeka Curriculum represents a breakthrough in Indonesia's education system, designed to create more flexible and student-centered learning. However, its implementation at the Madrasah Ibtidaiyah (MI) level faces various challenges. This study aims to analyze the challenges and opportunities in implementing the Merdeka Curriculum at MI Arrahman Palembang. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with the principal and two teachers, participatory observation, and document analysis. The findings reveal that the main challenges lie in the limitations of facilities and infrastructure, particularly reading spaces, information technology devices, and digital learning media, which hinder teachers' ability to utilize independent learning platforms. On the other hand, the Merdeka Curriculum provides opportunities for teachers to design more creative and contextual learning, as well as to develop a student-centered learning culture. The study concludes that the successful implementation of the Merdeka Curriculum requires enhancing educators' capabilities, systemic support from all stakeholders, and specific strategies to address infrastructure limitations. The implications of these findings recommend the importance of continuous mentoring and optimization of available resources to realize more adaptive and meaningful education.